Law and Language - Turaeva Umida Shukhratovna (Research Parks Publishers, 2023)
The use of language is crucial to any legal system, not only in the same way that it is crucial to politics in general, but also in two special respects. Lawmakers characteristically use language to make law, and law must provide for the authoritative resolution of disputes over the effects of that use of language. In this article, the role of legal terms in terminology, descriptions of legal language are presented based on cross-linguistic analysis. Also, the requirements for legal terms, features of translation of terms are covered in detail.